PSYCHO-EMOTIONAL DYNAMICS OF RETROSPECTIVE NARRATION IN DINA NAYERI'S NOVEL REFUGE - Чернишова, Світлана (Taras Shevchenko National University of Kyiv (Ukraine), 2022)
Migration has come to play an increasingly significant role in the 20th century and the beginning of the 21st century in politics, economics, geography, and culture. One of the main concepts of the migration literature is the concept of immigrant's identity. For an immigrant an ability to formulate a new identity goes through the process of embracing a sense of belonging to two or more cultures. It is important to consider that immigration and its depiction in the 21st fiction has gained new meaning. The convergence of migration and globalization has reshaped the understanding of immigrant's self. Conflicts between the native culture and the host one are transformed into dialogues. In the article we are referring to Amin Maalouf's idea about transnational or mixed identity. He argues for the multiple identities in contemporary societies. The same approach has been verbalized in the research of Carola Suárez-Orozco who proposes the concept of cosmopolitan identity which embraces the sense of belonging to a global culture of inclusion. Today the work of identity formation is to synthesize different cultures. The article sets out to explore the psycho-emotional dynamics in the retrospective narrative of Dina Nayeri's novel "Refuge". It is argued that the act of self-reflective retrospection entails a steady decrease in a temporal distance between the narrator and the narrated. In the act of remembering the past the narrator of the novel discloses not only the moments of resentment of her Iranian identity but comes to understanding that to move forward she needs to acknowledge her past. Psycho-emotional dynamics of her meetings with a father develops from the complete resentment to the recognition of her Iranian identity. The moral distance between the narrator and the narrated permitted by the temporal distance between the past and the present helps the main protagonist, Niloo, to understand her desire to distance herself from the Iranian past. She starts building her new identity after embracing her cultural heritage. It is concluded that immigrant's identity today is based on the productive dialogue between different cultures which are united in one traumatized body of an immigrant.

Міграційні процеси кінця ХХ – початку ХХІ ст. набули нового характеру та змісту. Нині у зв'язку з глобалізацією як економіки, так і культури іммігранти мають можливість перебувати у віртуальному полі вимушено покинутих країв. Цей факт змінює характер адаптації й позиціювання чужинців. Однак, одвічні питання самовизначення в реаліях нової країни проживання не полишають переміщених осіб. У романах, що написані на початку ХХІ ст., питання приналежності до і залежності від великих наративів нації, традиції, раси й етносу набувають нового значення. Їхнє осмислення змінюється: відмова від рідної спадщини на користь нових набутих культурних практик поступається місцем укладанню формату ідентичності, який охоплює різні парадигми й історії, що не конфліктують між собою, а доповнюють одні одних. Глобалізація та віртуальна культура сприяли тому, що самість іммігранта як загалом, так і в фікційному світі зокрема набула нового осмислення. Нині традиційне протистояння свій / чужий поступається місцем діалогу. Чужинець іде до своєї нової сутності через поєднання і примирення в собі кількох культур. Стверджується, що потреба повертатися до свого минулого і витлумачувати його знову під іншим кутом, реалізована у процесі ретроспективної нарації, становить домінантну рису сучасних міграційних романів. У фокусі уваги цієї статті роман сучасної ірано-американської письменниці Діни Найєрі "Притулок". Логіка наукового дослідження ґрунтується на теоретичних здобутках дослідників імміграції, наративної ідентичності, ретроспективної нарації. Остання має особливе значення для порозуміння між минулим і сучасним іммігранта. Через неодноразове переживання минулого в теперішньому відбувається процес об'єднання різних пластів пам'яті, від яких головна героїня роману прагнула відмовитися. Нілу, яка дитиною переїхала з матір'ю і братом до США, під час зустрічей із батьком поступово розуміє, що її минуле – невід'ємна частина сучасного. Зрештою, її ідентичність закорінена в іранському просторі, що набуває символічного значення як точка відліку складного пошуку себе у світі. Основний зміст спогадів головної героїні роману становлять зустрічі з батьком. Нілу переосмислює їхнє значення в момент ідентичнісної кризи. Порозуміння з батьком засвідчує її примирення з іранським минулим і його засвоєння.
ОСОБЛИВОСТІ РЕТРОСПЕКТИВНОЇ НАРАЦІЇ В РОМАНІ ДІНИ НАЙЄРІ "ПРИТУЛОК"
Keywords: immigrants' identity; retrospection; layers of the past; psycho-emotional dynamics of meetings; Dina Nayeri; Refuge; ідентичність іммігрантів; ретроспекція; пласти минулого; психо-емоційна динаміка зустрічей; Діна Найєрі; роман